A water-soluble hyperbranched copolymer based on a dendritic structure for low-to-moderate permeability reservoirs. Issue 39 (4th April 2016) - Lai, Nanjun; Zhang, Yan; Xu, Qian; Zhou, Ning; Wang, Hongjiang; Ye, Zhongbin
Abstract : An excellent matching relationship in size exists between HPDA and the pore throat with a permeability reservoir of under 500–100 mD. Abstract : In this study, a modified dendritic functional monomer (named DA) consisting of 1, 3-propanediamine as the initiated core was prepared and utilized to react with acrylamide (AM), acrylate (AA) and 2-acrylamido-2-methyl propane sulfonic acid (AMPS) to synthesize a water-soluble hyperbranched copolymer (noted HPDA) for low-to-moderate permeability reservoirs through a redox free radical polymerization strategy. The copolymer was characterized by a series of experiments, including IR, 1 H NMR, DLS and AFM. It was observed expectedly that the HPDA solution displayed a distinct topological structure in solution, resulting in a smaller mean diameter in comparison to the linear polymer. Furthermore, the rheology performances and anti-shearing properties of HPDA were investigated, which demonstrated that the introduced dendritic structure could endow the polymer with great viscosity retention and excellent elasticity in a relatively high frequency region. Based on the sand packed tube displacement experiment, a favorable matching relationship could be found between the size of the sheared HPDA and the pore throat as the permeability ranged from 500 to 100 mD. Moreover, compared with the linear polymer, AM/AA/AMPS, the sheared HPDA solution of 2000 mg L −1 could significantly increase the efficiency of oil recovery to 21.9% and 17.5% by controlling the displacing phase mobility and constructing an appreciable resistance factor and residual resistance factor in the 500 and 260 mD porous media.